Spoiled Friendships and Perverted Foods in Yōko Ogawa’s The Diving Pool - Lundquist, J (Pivot: A Journal of Interdisciplinary Studies and Thought, 2022)
This essay analyzes Yōko Ogawa’s The Diving Pool, in which the woman characters' ‘improper femininities’ are expressed through the rupturing of commensality. Ogawa's protagonists cause direct harm to those around them as a direct response to patriarchal norms of motherhood and child-rearing, as the novel explores how patriarchal capitalism and alienation destroy possibilities for female solidarity.